LENTIL RESILIENCE UNDER STRESS: IMPACT OF WATER AND SALT STRESS ON GERMINATION AND GROWTH OF FOUR GENOTYPES - Chebaani Meriem*; Nabi Fahima**,; Mouissa Habib*** (Natural Resources and Sustainable Development)
This study investigates the impact of water and salt stress, as well as their combined effect, on the germination and growth of four lentil genotypes (Lens culinaris Medik.): Syrie299, Métropole, LVS, and IBLa1. Water stress was simulated using polyethylene glycol 6000 (PEG6000) solutions at 10% and 15%, while salt stress was induced with NaCl at 50 and 100 mM. The combined effect of both stresses was also examined. Results show that both stress types significantly reduce final germination percentage (FGP), and germination speed (GS). Under water stress, Syrie299 maintained high germination (68.33% at 15% PEG6000), while IBLa1 showed increased sensitivity (45%). At 100 mM NaCl, all genotypes experienced a significant drop in FGP, with Métropole showing the lowest rate (1.67%). Under combined stress (15% PEG + 100 mM NaCl), LVS exhibited extreme sensitivity (FGP of 15%), while Syrie299 retained relative tolerance with an FGP of 78.33%. In conclusion, this study highlights the negative impact of water and salt stress on lentil germination and growth, particularly under combined stress conditions. Syrie299 and Métropole emerge as more tolerant genotypes, making them promising candidates for breeding varieties suited to arid environments.